DIVISION OF RETAINED EARNINGS TO REFLECT BUSINESS NEEDS. - Brown, Harry G. (The Accounting Review, 1957)
Abstract Earnings may be retained for a variety of reasons, some obvious and definite, others more difficult to analyze and to measure. Faced with the need to reflect information about the retention of earnings on financial statements, accountants have resorted to the use of reserves to accomplish this task. According to John A. Beckett retained earnings can be subjected to critical analysis for the benefit of management and other interested parties by indicating the reasons for retention of undistributed earnings. The normal problem of replacement is accentuated when a decline in the purchasing power of the dollar takes place. Since the subdivision of retained earnings will reflect both past accomplishments and future plans, it is doubtful if in many cases the un-appropriated balance will be large enough to warrant questioning by the Tax Department under the accumulated earnings tax provisions. This assumes, that the corporation presents substantial and acceptable evidence of serious intent to support its functional breakdown of retained earnings.